The impact of time management on activating the professional skepticism of the auditor - Hussein Ali Mohammed (Technium EconomiA, 2024)
The research aimed to identify the role of time management in activating and achieving professional skepticism for auditors and applying it in some auditing offices in Baghdad, to raise the quality of auditors' judgments, with the increasing pressures on the profession of auditors and the quality of the auditing process as a whole, there is a continuous need to rationalize the decisions of auditors' report users, as international accounting standards emphasized the need to direct continuous inquiries about information in auditor practices, which makes professional skepticism one of the important tools of the auditing profession, the research community was selected for a group of auditors in the Iraqi environment where the sample for the research community was (45) licensed audit offices in Baghdad with certificates of certified public accountant (accountant), and the research used a questionnaire form that was distributed to them, which is a tool for collecting data that is consistent with the research objectives, and (39) were retrieved, but (6) questionnaires were not used from the research sample, and the descriptive analytical approach was used based on the (SSPS) program to analyze the results of the answers. One of the most important results of the research is that managing the activities and work of auditors at a planned and organized time contributes to completing their tasks effectively and reduces time pressure and allows By practicing professional skepticism, which improves the reputation of the profession, and among the research recommendations is the need for audit offices to pay attention to educational courses for auditors, which include consolidating the conviction of the importance of time management and getting rid of false arguments that lead to wasting time when practicing professional skepticism. The researcher also recommended the need to urge auditors to pay attention to professional skepticism in all stages of the auditing process. To achieve the objectives of the research, it was divided into four chapters. The first chapter included the methodology and previous studies, while the second chapter included the theoretical aspect of the research, while the third chapter included the practical aspect of the research, and finally the fourth chapter included the most important recommendations and conclusions.